2004
DOI: 10.1128/aem.70.10.5778-5786.2004
|View full text |Cite
|
Sign up to set email alerts
|

Stable-Isotope Probing of Microorganisms Thriving at Thermodynamic Limits: Syntrophic Propionate Oxidation in Flooded Soil

Abstract: Propionate is an important intermediate of the degradation of organic matter in many anoxic environments. In methanogenic environments, due to thermodynamic constraints, the oxidation of propionate requires syntrophic cooperation of propionate-fermenting proton-reducing bacteria and H 2 -consuming methanogens. We have identified here microorganisms that were active in syntrophic propionate oxidation in anoxic paddy soil by rRNA-based stable-isotope probing (SIP). After 7 weeks of incubation with [ 13 C]propion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
142
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 65 publications
5
142
0
Order By: Relevance
“…Using rice paddy soil as microbial inocula, Kato et al [19] reported the syntrophic association between Geobacter and Methanosarcina in the presence of hematite and magnetite; methanogenesis was facilitated via DIET through (semi) conductive iron oxides. In this study, Methanosarcina and Methanobacterium are detected as the most abundant methanogens in the soil cultures, similar to other rice paddy soils [9,29,52]. T-RFLP results showed that the amendment of AQDS (0.5 and 5 mM) led to increased relative abundance of Methanosarcina at the expense of Methanobacterium.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Using rice paddy soil as microbial inocula, Kato et al [19] reported the syntrophic association between Geobacter and Methanosarcina in the presence of hematite and magnetite; methanogenesis was facilitated via DIET through (semi) conductive iron oxides. In this study, Methanosarcina and Methanobacterium are detected as the most abundant methanogens in the soil cultures, similar to other rice paddy soils [9,29,52]. T-RFLP results showed that the amendment of AQDS (0.5 and 5 mM) led to increased relative abundance of Methanosarcina at the expense of Methanobacterium.…”
Section: Discussionsupporting
confidence: 80%
“…The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27]. There is increasing evidence that Geobacter species are important syntrophic microorganisms capable of establishing syntrophic association with methanogens [19,29,45]. Recent study demonstrated the possibility of direct interspecies electron transfer (DIET) between Geobacter species and Methanosaeta concilii within upflow anaerobic sludge blanket reactor methanogenic aggregates, which were electrically conductive largely contributed by Geobacter species [32].…”
Section: Discussionmentioning
confidence: 99%
“…Members of RC-I are hydrogenotrophic and more active at low H 2 concentrations , which allows them to grow in syntrophy with secondary fermenters (Lueders et al, 2004). RC-I is often found in periodically oxic environments, suggesting that they are well adapted to oxic stress during periods of drought .…”
Section: Discussionmentioning
confidence: 99%
“…Rice field soil slurry was prepared as described earlier (Hori et al, 2007). To activate the soil microorganisms and reduce endogenous electron acceptors such as available sulfate and ferric iron oxides, the slurry was pre-incubated for 21 days in the dark at 25 1C Friedrich, 2000, 2002;Lueders et al, 2004b). Aliquots (10 ml) of the homogenized slurry were transferred into 25-ml serum vials.…”
Section: Methodsmentioning
confidence: 99%